Resistance to Striga hermonthica in a maize inbred line derived from Zea diploperennis - Amusan, I.O.; Rich, P.J.; Menkir, A.; Housley, T.; Ejeta, G. (Wiley, 2008)
• Breeding for resistance to Striga in maize (Zea mays), with paucity of donor source and known mechanisms of resistance, has been challenging. • Here, post-attachment development of S. hermonthica was monitored on two maize inbreds selected for field resistance and susceptibility reactions to Striga at the International Institute of Tropical Agriculture. Haustorial invasion of the parasite into roots of these inbreds was examined histologically. • Morphological differences were observed between roots of the susceptible and the resistant inbreds. The resistant maize had fewer Striga attachments, delayed parasitic development and higher mortality of attached parasites compared with the susceptible inbred. Striga on the susceptible inbred usually penetrated the xylem and showed substantial internal haustorial development. Haustorial ingress on the resistant inbred was often stopped at the endodermis. Parasites able to reach resistant host xylem vessels showed diminished haustorial development relative to those invading susceptible roots. • These results suggest that the resistant inbred expresses a developmental barrier and incompatible response against Striga parasitism.